Zeolite supplementation effects on lamb growth and gastrointestinal nematode infection, and economic analysis - Novita Esteves, Sérgio (Revista Ciência Agronômica, 2021)
Zeolite as a dietary supplement can improve animal resistance and resilience against gastrointestinal parasites. Theeffects of different levels of zeolite supplementation on gastrointestinal nematode infection, growth performance, and economicviability of male and female Santa Ines lambs were investigated. Four zeolite levels (0, 25, 50, and 75 g per day) were fed to 110day-old animals in a randomized block experimental design. Eggs per gram of feces (EPG), total serum protein (TSP), and packed cellvolume (PCV) were measured individually every week. The animals were weighed every 14 days and coprocultures were prepared.Male animals that reached an average live weight of 34 kg were harvested. The economic viability analysis of the experimental dietswas based on feedlot periods of 56 and 91 days. Dietary supplementation with zeolite did not signifi cantly mitigate infections bynematodes and did not affect TSP, PCV, or feedlot lamb growth performance. Therefore, zeolite was not an effective (P > 0.05) dietarysupplement for avoiding gastrointestinal nematode infection or improving growth performance. Male animals slaughtered after 56 daysof feeding were more economically viable (P < 0.05) than those slaughtered after 91 days. Feedlotting demonstrated that male animalshad superior performance (P < 0.05) and better economic (P < 0.05) results than female animals.